Donald Trump 37-count felony indictment unsealed in documents case - Churm, Philip Andrew (euronews, 2023)
Former US president Donald Trump has become the first US ex-president to face federal indictment following the seizure of classified documents from his Mar-a-Lago estate.
Keywords: 2023-06 June